2004
DOI: 10.1128/jvi.78.23.13019-13027.2004
|View full text |Cite
|
Sign up to set email alerts
|

Structural Protein Requirements in Equine Arteritis Virus Assembly

Abstract: Equine arteritis virus (EAV) is an enveloped, positive-stranded RNA virus belonging to the family Arteriviridae of the order Nidovirales. EAV particles contain seven structural proteins: the nucleocapsid protein N, the unglycosylated envelope proteins M and E, and the N-glycosylated membrane proteins GP 2b (previously named G S ), GP 3 , GP 4 , and GP 5 (previously named G L ). Proteins N, M, and GP 5 are major virion components, E occurs in virus particles in intermediate amounts, and GP 4 , GP 3 , and GP 2b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
116
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 39 publications
3
116
0
Order By: Relevance
“…Envelope protein E is a small, unglycosylated hydrophobic protein necessary for the correct assembly of the EAV virion (23). It was previously demonstrated (4) that ORF2a, encoding protein E, was one of the most conserved genes during persistent infection with only 3 synonymous substitutions found in the course of a 5-year observation.…”
Section: Discussionmentioning
confidence: 99%
“…Envelope protein E is a small, unglycosylated hydrophobic protein necessary for the correct assembly of the EAV virion (23). It was previously demonstrated (4) that ORF2a, encoding protein E, was one of the most conserved genes during persistent infection with only 3 synonymous substitutions found in the course of a 5-year observation.…”
Section: Discussionmentioning
confidence: 99%
“…For EAV, GP 2b , GP 3 , and GP 4 have been reported to exist as covalently linked heterotrimeric complexes (45). Furthermore, incorporation of these glycoproteins and of the E protein in EAV particles was shown to be interdependent (43). The GP 5 and M proteins exist as disulfide-linked heterodimers in PRRSV particles (20).…”
mentioning
confidence: 99%
“…Using an European PRRSV isolate, Wissink et al (2004) have described a heterotrimeric complex of GP2, GP3 and GP4 and, without evidence, speculated a possible incorporation of E protein with this trimeric complex. Wieringa et al (2004) have recently shown a covalent association of the E protein with the GP2b-GP3-GP4 heterotrimers in EAV, suggesting a possible role of the heteromultimeric complex in the virus entry process. It is noteworthy that E proteins of European PRRSV and EAV contain a single cysteine at positions 51 and 58, respectively, which corresponds to position 54 in the North American PRRSV genotype (Fig.…”
mentioning
confidence: 99%